First record of the genus Pseudomesochra T. Scott (Harpacticoida: Pseudotachidiidae)in the South Atlantic with description of a deep-sea species: Pseudomesochralongiseta sp. nov. - Vasconcelos, Danielle Menor; George, Kai Horst; Parreira Dos Santos, Paulo Jorge (Zootaxa, 2008)
Samples collected during the Sergipe Continental Slope Environmental Characterization Project coordinated by PETROBRAS (The Brazilian Petroleum Company) revealed a new species of the family Pseudotachidiidae Lang, 1936 (Copepoda, Harpacticoida), Pseudomesochra longiseta sp. nov. This is the first record of the genus Pseudomesochra T. Scott, 1902 for the South Atlantic. Pseudomesochra longiseta sp. nov. can be distinguished from all species of the genus Pseudomesochra by the presence of four sensilla on the rostrum and a very long terminal “rat-tail” seta on the second segment of the antenna. It shares with P. tamara Smirnov, 1946 the addition of one inner seta on the first exopodal segment of the swimming legs 2–4 (P2–P4), a character absent in the remaining species of the genus. Pseudomesochra longiseta sp. nov. is the fourth species described within this genus with 2-segmented P2–P4 endopods. The inclusion of the new species in Pseudomesochra requires the modification of some autapomorphic characters of the genus, the most important being the presence of four sensilla on the rostrum, a character shared with other Pseudotachidiidae.